Exploring the Impact of Trust, Perceived Utility, Ease of Use Perception, and Social Influence on E-Payment Adoption - Lissa Rosdiana Noer; Jihan Fadhilah; Prahardika Prihananto; Bustanul Arifin Noer (Jurnal Sosial Humaniora, 2023)
Consumer behavior shifts from cash to digital transactions due to innovationsin payment system digitization, primarily through electronic payments likemobile banking and electronic wallets. In Indonesia, Shopee Pay emerged as aprominent non-bank QRIS provider in 2021, with the Quick Response CodeIndonesia Standard (QRIS) mandated for all payment service providers.QRIS usage potential is high in East Java, particularly in Surabaya, whereGeneration Z constitutes the dominant user group for digital payments. Tounderstand the factors influencing Generation Z's e-payment adoption, astudy investigated the impact of payment mediums (Shopee Pay and mobilebanking) on key variables: trust, perceived usefulness, perceived ease of use,social influence, intention to use, and actual usage of e-payment. UsingStructural Equation Modeling (SEM) and Multi-Group Analysis (MGA) on390 data points, the study revealed that trust, perceived usefulness, perceivedease of use, and social influence significantly influence intention to use,subsequently affecting actual e-payment usage. Furthermore, the study foundthat the effect of payment media on the relationship between trust andintention to use is notable only in mobile banking, whereas social influence'simpact on intention to use is significant exclusively for Shopee Pay, asindicated by MGA results.